THE EFFECT OF VISIONARY LEADERSHIP, ORGANIZATIONAL BEHAVIOR, PERSUASIVE COMMUNICATION AND ORGANIZATIONAL COMMITMENT ON THE PROFESSIONALITY OF HONORARY EMPLOYEES - Asad Isma; Dedi Purwana; Muchlis R.Luddin (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The objective of this research is to study the effect of visionary leadership, organizational behavior, persuasive communication and organizational commitment on the professionality. The research approach is quantitative and the analysis method used is path analysis The research was conducted at IAIN Sulthan Thaha Saifuddin located in Jambi, using survey with the samples of 87 employees being selected randomly.The research findings show: (1) visionary leadership has positively and significantly affected the professionality; (2) organizational behavior has positively and significantly affected the professionality; (3) organizational behavior has positively and significantly affected the organizational commitment; (4) persuasive communication has positively and significantly affected the organizational commitment. Based on these findings, it can be concluded that enhancing the professionality can be done through strengthening leadership and improving organizational behavior. It was also obtained that (1) professionality was not significantly influenced by organizational commitment and persuasive communication, and (2) organizational commitment was not significantly influenced by visionary leadership. Keywords: professionality, visionary leadership, organizational behavior, persuasive communication, organizational commitment